Drive better, feel better: Examining associations between well-being and driving behaviour in students - Bowen, Louise; Smith, Andrew (Advances in Social Sciences Research Journal, 2019)
Road transport often presents one of the major safety risks to which individuals are exposed. In the present study, driving behaviour, driving skill, driving hazards and their potential links to well-being were examined in a sample of 224 undergraduate psychology students at Cardiff University. A cross-sectional, online survey measured driving behaviour (e.g., distraction and aggression - derived from the recent work of Smith, 2016) and well-being (positive outcomes, negative outcomes, and positive and negative appraisals) using the Student-WPQ (Williams et al., 2017). Hierarchical multiple regressions demonstrated that poor driving behaviour predicted negativewell-beingandappraisal,whereasmorepro-socialdriving behaviourwaspredictiveofpositivewell-being and appraisal. These effects remained significant when established predictors of well-being were covaried. Therefore, this research has identified links between well-being and driving behaviour. While it is acknowledged that the cross-sectional nature of the research makes attribution of causality problematic, it is suggested the identification of potential variables of interest paves the way for further longitudinal enquiry.